Analisis Semiotika Makna Pesan “Orang Pintar Minum Tolak Angin” dalam Iklan Produk Herbal Tolak Angin - Sabrina Puspita Sari; Arfian Suryasuciramdhan; Gandhes Lintang Pangestu; Chitra Cahya Anggraeni; Noviatul Fitri (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
. Advertisement is a communication tool containing symbolic messages to shape consumer perception and persuade behavior. One of the notable advertisements is the herbal product Tolak Angin, with the slogan “Orang Pintar Minum Tolak Angin”. The purpose of this study is to analyze the meaning of the messages contained in the slogan and how this advertisement forms a consumer image through the symbols and narratives conveyed. This research uses a descriptive qualitative approach with a literature review method and Roland Barthes' semiotic theory as an analysis knife. This theory is used to see meaning through three layers, namely denotation, connotation, and myth. Tolak Angin advertisements are analyzed based on visual elements, character expressions, colors, verbal text, and other symbols that appear in the broadcast. The result shows that the advertisement constructs an image of a smart, modern, and health-conscious consumer through symbolic representation. It also creates a myth that consuming herbal medicine is a sign of intelligence and awareness of healthy living.